Do Dividend Clienteles Exist? Evidence on Dividend Preferences of Retail Investors - GRAHAM, JOHN R.; KUMAR, ALOK (Journal of Finance, 2006)
ABSTRACT We study stock holdings and trading behavior of more than 60,000 households and find evidence consistent with dividend clienteles. Retail investor stock holdings indicate a preference for dividend yield that increases with age and decreases with income, consistent with age and tax clienteles, respectively. Trading patterns reinforce this evidence: Older, low‐income investors disproportionally purchase stocks before the ex‐dividend day. Furthermore, among small stocks, the ex‐day price drop decreases with age and increases with income, consistent with clientele effects. Finally, consistent with the behavioral “attention” hypothesis, we document that older and low‐income investors purchase stocks following dividend announcements.